Eudorylaimus kahaqensis sp. n. (Nematoda: Dorylaimida: Qudsianematidae), an interesting new species from Iran - Kazemi, E.; Niknam, G.; Jabbari, H.; Peña-Santiago, R. (Zootaxa, 2018)
A new species of the genus Eudorylaimus is described from Kahaq region, Maragheh, East Azarbaijan province in Iran. Eudorylaimus kahaqensis sp. n. is characterized by its 1.40–1.75 mm long body, lip region nearly continuous and 17–21 µm wide and bearing a weakly sclerotized but distinct cephalic framework, cheilostom broad and with convex walls, odontostyle 21–23 µm long with aperture occupying 33–44% of its length, presence of a dorsal coelomocyte a short distance behind the nerve ring, neck 347–397 µm long, DN rather posterior (66–70%), pharyngeal expansion 162–205 µm or occupying 45–53% of total neck length, presence a dorsal cell mass at level of pharyngo-intestinal junction, V = 48–52, caudal region conical elongate (50–73 µm, c = 24–30, c’ = 1.9–2.6 in females; 45–68 µm, c = 22–32, c’ = 1.7–2.3 in males) and regularly curved ventrad with large hyaline portion, spicules 48–55 µm long and 7–9 irregularly spaced ventromedian supplements lacking hiatus.